Comparing the effectiveness of explicit EAL feedback through slideshow (text+audio) and captioned video - Jonathan Harrison (English Language Teaching Educational Journal, 2022)
Research seems to show that captions and subtitles are generally beneficial to learners of English as an Additional Language (EAL), but some research does contradict this. Research on slideware and slide design seems to focus more on attractiveness of slides and less on educational effectiveness. However, research on slide design and specific approaches to slide design continue to become more detailed. This study compared comprehension of explicit feedback received through either slideshow (text+audio) video or captioned video on an EAL writing task in an on-demand university setting. Results (n=163) indicated that approximately 50% of learners clicked the feedback video to advance to the quiz without viewing it completely. Of the learners with at least one full viewing (n=86), slideshow video seems to have engaged students for a longer duration than captioned video. The quiz items were easier for the slideshow video groups, and the quiz items performed better for these groups. The slideshow video groups had slightly higher means, but a significant difference between the effectiveness of slideshow video and captioned video to transmit feedback to students was not found.